Optimization of injection moulding parameters using Cadmould simulation software for Cover Fog Lamp / Mohammad Marzuki Ashari - Ashari, Mohammad Marzuki (2008)
This study was conducted to optimize injection moulding parameter using Cadmould simulation software for Cover Fog Lamp. Cover Fog Lamp parts for model MYVI SE2 (D96T) is simulate by using Cadmould. Cadmould is CAE software that uses to simulate plastic flow during injection moulding process. Cover Fog Lamp is made by using Polypropylene materials grade OX544M2AM4 BUB6UV producing by company name Colouring and Compounding Sdn. Bhd. In this study, the parameters chosen were filling time, packing time, and cooling time. This parameter was varied and their effect on shrinkage and warpage was simulated. Based on this study, it was found that the increasing of filling time (injection speed), packing time, and cooling time will minimize the shrinkage. Besides that, the defect such as sink mark that detected using Cadmould simulation appears on the actual process. The dimension of part that determine by using simulation is almost same to the actual dimension. This simulation process also detected unbalance filling that occurs in the actual process. Generally, it can be concluding that the CAE simulation technique was useful to optimize the injection moulding parameter in order to obtained perfect parts.